Air Force civilian to airman - Goldish, Meish (Bearport, 2011)
A line of air force trainees hung from the monkey bars, high above a muddy pit. They held on tightly as they tried to pull themselves all the way across the bars to the other side of the pit. Though they were exhausted and their hands burned, they didn't dare let go. One slip and they would fall into the mud-and have to start all over again. This exercise is just one of many demanding tests that air force trainees go through during basic military training. Look inside to learn more about what it takes for civilians to become airmen in the U.S. Air Force.